2016
DOI: 10.1038/srep32473
|View full text |Cite|
|
Sign up to set email alerts
|

Weibel-Palade body size modulates the adhesive activity of its von Willebrand Factor cargo in cultured endothelial cells

Abstract: Changes in the size of cellular organelles are often linked to modifications in their function. Endothelial cells store von Willebrand Factor (vWF), a glycoprotein essential to haemostasis in Weibel-Palade bodies (WPBs), cigar-shaped secretory granules that are generated in a wide range of sizes. We recently showed that forcing changes in the size of WPBs modifies the activity of this cargo. We now find that endothelial cells treated with statins produce shorter WPBs and that the vWF they release at exocytosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
109
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(119 citation statements)
references
References 61 publications
8
109
1
1
Order By: Relevance
“…This approach revealed that trafficking fellows are transported together as subpools of cargos through the Golgi complex. He further showed that (Ferraro et al, 2016). Changes in Golgi organization, in particular its disassembly in early mitosis, also appear to have a role in controlling mitotic spindle assembly, as shown by Joachim Seemann (UT Southwestern, Dallas, USA) (Guizzunti and Seemann, 2016).…”
Section: Secretion: Making Proteins and Membranes And How To Get Themmentioning
confidence: 93%
“…This approach revealed that trafficking fellows are transported together as subpools of cargos through the Golgi complex. He further showed that (Ferraro et al, 2016). Changes in Golgi organization, in particular its disassembly in early mitosis, also appear to have a role in controlling mitotic spindle assembly, as shown by Joachim Seemann (UT Southwestern, Dallas, USA) (Guizzunti and Seemann, 2016).…”
Section: Secretion: Making Proteins and Membranes And How To Get Themmentioning
confidence: 93%
“…A quantitative high-throughput microscopy-based workflow, dubbed highthroughput morphometry (HTM), allows rapid quantification of the size of tens to hundreds of thousands of WPBs within thousands of endothelial cells (Ferraro et al, 2014). HTM has been applied for analytical purposes and in phenotypic screens (Ferraro et al, 2014;Ferraro et al, 2016;Ketteler et al, 2017;Lopes-da-Silva et al, 2019;Stevenson et al, 2014). In the present report, HTM was deployed to identify compounds that can induce a reduction of WPB size in Human Umbilical Vein Endothelial Cells (HUVECs).…”
Section: Screenmentioning
confidence: 99%
“…Their size depends on the structural status of the endothelial Golgi apparatus where they form, and experimental manipulations causing Golgi fragmentation consistently result in the formation of only short WPBs (Ferraro et al, 2014). Short WPBs also form when VWF biosynthesis by endothelial cells is reduced, or following statin treatment, via Golgi fragmentation-independent and -dependent mechanisms, respectively (Ferraro et al, 2014;Ferraro et al, 2016). The metabolic status of endothelial cells also regulates WPB size through an AMPK-mediated signalling pathway (Lopes-da-Silva et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The homotypic connections between adjacent cisternae of the stacks enlarge the membrane compartment such that large cargos as collagen can be readily accommodated [10,11*]. Similarly, a continuous ribbon allows proper packing of the von Willebrand factor into larger Weibel-Palade bodies, which impacts platelet aggregation [12**,13]. Furthermore, by laterally linking stacks, the Golgi apparatus is consolidated into one single entity that in most cases is asymmetrically positioned in the juxtanuclear region and in close proximity to centrosomes, the primary microtubule-organizing center (MTOC) in proliferating cells [6].…”
Section: Structure and Function Of The Golgi Apparatusmentioning
confidence: 99%